A Comparison of Existing Coordinate Transformation Models and Parameters in Australia - Featherstone, Will (Mapping Sciences Institute Australia, 1997)
Four standard procedures to transform curvilinear co-ordinates from the Australian Geodetic Datum 1984 to the World Geodetic System 1984 are compared. These comprise the Bursa-Wolf model with the national set of seven parameters currently used by Federal and State surveying and mapping authorities, the standard Molodensky model with the five parameters used by the United States Defense Mapping Agency, the simple three-parameter model with the origin shifts taken from the Bursa-Wolf and standard Molodensky models, and the multiple regression equations as determined by the Defense Mapping Agency. The differences between the resulting co-ordinates can reach 4.2 metres over continental Australia, which has implications for the final approach adopted to transform to the Geocentric Datum of Australia. The arguments are presented in favour of more suitable transformation strategies using projective transformation models, which are able to simultaneously correct any known errors existing in the Australian Geodetic Datum. These models also allow the direct transformation of both Australian Geodetic Datum 1966 and Australian Geodetic Datum 1984 co-ordinates in a single procedure, which will be of benefit to those States which rely upon older geodetic datums.